The Role of Language in Education: Arabic as Case Study - Zedan, A.M.; Kadir, F.A.A.; Yusof, M.; Yusmini, M.Y.; Siren, N.H.; Mohamed, R.; Toure, S. (Elsevier, 2013)
It is obvious that languages play an important role in various aspects of our daily lives. Their role is not only limited to communication, rather it extends into the vast branches of knowledge and human sciences. Languages are capable of developing human knowledge and extending it for the benefit of human kind. The general importance of languages justifies the need for a scientific and objective study of the relationship between languages and education.